The dynamic relationship between investments in brand equity and firm profitability: Evidence using trademark registrations - Dirk Crass; Dirk Czarnitzki; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Most marketing practitioners and scholars agree that marketing assets such as brand equity significantly contribute to a firm's financial performance. In this paper, we model brand equity as an unobservable stock that results from up to thirty years of past brand-related investment flows. Using firm-specific trademarks as investment proxies, our results show a significant long-run impact on financial performance. The dynamic profile of brand-related investments has an inverted-U shape that reaches its peak after eleven years. On average, it takes four years before brand related investments show a positive return, and investments older than nineteen years show no significant impact. For the median trademarking firm, brand equity contributes 265,000 Euro to annual profits.
urn:nbn:de:bsz:180-madoc-405877
Keywords: O31; O34; 330; Brand Equity; Firm Profitability; Intellectual Property Rights; Trademarks